Polyglactin 910 (Vicryl Rapide) for Reducing Pain and Wounds Healing in Postpartum Perineum: Polyglactin 910 (Vicryl Rapide) untuk Mengurangi Nyeri dan Mempercepat Penyembuhan Luka pada Perineum Postpartum - amilya pradita; Abkar Raden; Farida Kartini (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: The purpose of this study was to compare the use of polyglactin 910 (vicryrapide) and chromic catgut to perineal pain and healing wounds on postpartum. Method: This research is true experiment with a randomized controlled trial (RCT) and single-blind. The number of respondents pad this study of 40 respondents were divided into 20 respondents to the intervention group (vicrylrapide) and 20 respondents for the control group (chromic catgut). Data analysis using independent t-test. Results: Statistical test results using independent t-test for pain showed p = 0.035 <0.05 and for wound healing showed p = 0.000 <0.05 of a second can mean the results are there differences in the use of threads polyglactin 910 (vicrylrapide) and chromic catgut thread to perineal pain and healing wounds in the mother postpartum perineum. Conclusion: The use rapidevicryl thread to repair perineal perineum or stitches can reduce perineal pain and healing wounds better than the use of the chromic catgut thread. Keywords: chromic catgut, pain, polyglactin 910, rapide vicryl, wound healing of the perineum. Abstrak Tujuan: Untuk mengetahui perbandingan penggunaan polyglactin 910 (vicry rapide) dan chromic catgut terhadap nyeri dan penyembuhan luka perineum pada postpartum. Metode: Penelitian ini merupakan penelitian true experiment dengan randomized controlled trial (RCT) dansingle blind. Jumlah responden pada penelitian ini sebanyak 40 responden yang di bagi menjadi 20 responden untuk kelompok intervensi (vicryl rapide) dan 20 responden untuk kelompok kontrol (chromic catgut ). Analisis data menggunakan independent t-test. Hasil: Uji statistik menggunakan independent t-test untuk nyeri didapatkan hasil p=0,035<0,05 dan untuk penyembuhan luka didapatkan hasil p=0,000<0,05 dari kedua hasil tersebut dapat diartikan ada perbedaan penggunaan benang polyglactin 910 (vicryl rapide) dan benang chromic catgutterhadapnyeri perineum dan penyembuhan luka perineum pada ibu postpartum. Kesimpulan: Penggunaan benang vicryl rapide untuk perbaikan perineum atau penjahitan luka perineum dapat mengurangi nyeri perineum dan penyembuhan luka yang lebih baik dibandingkan dengan penggunaan pada benang chromic catgut. Kata kunci: chromic catgut, nyeri, penyembuhan luka perineum, polyglactin 910, vicryl rapide.